2007
DOI: 10.1197/jamia.m2271
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Order Entry with Decision Support for Chronic Care by Physician Organizations

Abstract: Because external incentives are strong drivers of adoption, policies requiring reporting of chronic care measurements and rewarding improvement as well as financial incentives for use of specific information technology tools are likely to accelerate adoption of order entry with decision support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Chart review is labor-intensive and is associated with significant costs, which may limit the use of these quality measures for general application. We think that, with the increasing adoption of electronic medical records, 47,48 standard data elements necessary to generate these measures could be incorporated into an electronic medical record, to collect data at the point of care and to decrease the burden associated with manual chart review.…”
Section: Discussionmentioning
confidence: 99%
“…Chart review is labor-intensive and is associated with significant costs, which may limit the use of these quality measures for general application. We think that, with the increasing adoption of electronic medical records, 47,48 standard data elements necessary to generate these measures could be incorporated into an electronic medical record, to collect data at the point of care and to decrease the burden associated with manual chart review.…”
Section: Discussionmentioning
confidence: 99%
“…Rewarding and financial incentives accelerate adoption of computerized physician order entry with clinical decision support systems [31]. Gagnon et al found that social norms are one of the significant predictors of physicians' intention toward medical technology usage [16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Non-visit care, such as phone communication and electronic mail, is not generally reimbursed, so strong incentives exist for providers to delay EMR implementation. Rewarding practices for publishing performance reports and mandating specific quality improvement tactics or IT applications could hasten implementation (Miller & Sim, 2004; Simon, Rundall, & Shortell 2007). Financial resources need to be available for under-resourced settings to partner with local organizations, businesses, and government organizations to install EMRs, participate in regional HIEs, and use innovative health IT applications to improve patient outcomes (Goroll, Simon, Tripathi, Ascenzo, & Bates, 2009; McDonald et al, 2005; Mostashari, Tripathi, & Kendall, 2009).…”
Section: Discussionmentioning
confidence: 99%